Evaluation of the Efficiency of the Prison Programs for Ex-Prison Convicts to Integrate in Society upon Their Release in Zanzibar - Makungu, Seif (Journal of Public Policy and Administration, 2025)
Purpose: This study explores the efficiency of the prison programs for ex-prison convicts to integrate into society upon their release in Zanzibar, Tanzania. The target population was the ex-offenders, prison officials and community. Methodology: The study employed questionnaires and interview which were conducted to ex-prisoners, prison officials, member of the community, focal group discussions and observations and data were analyzed thematically. A sample size of 104 participants and respondents were involved in the study. Findings: The study Findings showed that that majority of the people agreed that, the authority have capacity to change the behavior of the prisoners in Zanzibar. This has been revealed to the study findings which show that 81 respondents out of 104 which is equal to 77.9% of the total study respondents agreed and twenty three (22.1%) respondents who did react by saying disagreed. This means to say that capacity of the authority had nothing to contribute on the behavior change of the prisoners in Zanzibar. Also, the study findings disclosed that majority of the people agreed that, there are some challenges face the prison authority in dealing with the behaviour of the prisoners to be law abiding citizens and avoid re-offending tendency in Zanzibar. This has been discovered by the study findings which indicates that sixty six respondents out of 104 which is equal to 58.7% from the total study respondents and forty three (41.3%) respondents disagree. The study recommends that the government should solve the challenges facing prison authority to perform its activities effectively. Also the government should continue with its effort by making collaboration with national and international stakeholders to be able to provide more effective rehabilitation programs. Unique Contribution to Theory, Practice and Policy: The study recommends that the government should solve the challenges facing prison authority to perform its activities effectively, also the government should continue with its effort by making collaboration with national and international stakeholders to be able to provide more effective rehabilitation programs on other hand the community has to support government in fighting against crime, receiving and educating the ex-prisoners, teaching the children good behavior and maintaining cultural identity, call for the legal reforms to address the issues of rehabilitation and reintegration in generally.